Hubungan antara Intensitas Bermain Game Roblox dengan Keterampilan Menulis Karangan Narasi pada Siswa Kelas IV-VI Sekolah Dasar - Anggraeni, Leni; Purnanto, Arif Wiyat; Wijayanto, Sukma (Borobudur Educational Review, 2026)
This study aims to examine the relationship between the intensity of playing Roblox and the narrative writing skills of fourth to sixth grade elementary school students in the Semangat Cluster, Secang District. The research employed a quantitative approach with a correlational method. The participants consisted of 64 students. Data were collected through a questionnaire measuring the intensity of playing Roblox and a performance test assessing narrative writing skills, and were analyzed using the Pearson Product Moment correlation test with the assistance of IBM SPSS Statistics 27. The results revealed a correlation coefficient of r = 0.344 with a significance value of p = 0.005 (p < 0.01), indicating a positive and statistically significant relationship in the weak category between the two variables. The coefficient of determination (11.8%) indicates that the intensity of playing Roblox contributes 11.8% to the variance in students’ narrative writing skills, while 88.2% is influenced by other factors beyond the scope of this study. Therefore, it can be concluded that a positive and statistically significant relationship at a weak level exists between the intensity of playing Roblox and students’ narrative writing skills.